Eribulin mesylate in advanced breast cancer: retrospective review of a single institute experience. (August 2015) - Martella, Francesca; Bacci, Carlotta; Giordano, Clara; Montagnani, Francesco; Gelain, Elena; Rabatti, Loredana; Fioretto, Luisa
Aim: EMA licensed eribulin mesylate in 2011 for women with advanced breast cancer already treated with at least two lines of chemotherapy, including anthracyclines and taxanes. Azienda Sanitaria Firenze experience is reported to assess the efficacy and safety of eribulin in the real-life setting.Patients & methods: Eribulin was infused as per indication. All women treated in the last 2 years were reviewed.Results: A total of 27 women received eribulin. All but one was pretreated with anthracyclines, 97% with taxanes and 87% with capecitabine. Median age was 63 years (range: 27–80). A median of four cycles of eribulin were infused (range: 2–10). Overall response rate was 30% with a 45% of clinical benefit (response plus stable disease for at least 24 weeks). Toxicities have been as expected. Severe toxicities were rare, with one patient experiencing sepsis and 18% developing grade 3 asthenia.Conclusion: Eribulin maintains its activity out of clinical trials, without unexpected toxicities.